Plant-based diets to manage the risks and complications of chronic kidney disease - Carrero, Juan J; González-Ortiz, Ailema; Avesani, Carla M; Bakker, Stephan J L; Bellizzi, Vincenzo; Chauveau, Philippe; Clase, Catherine M; Cupisti, Adamasco; Espinosa-Cuevas, Angeles; Molina, Pablo; Moreau, Karine; Piccoli, Giorgina B; et al. (Nature reviews. Nephrology, 2020)
Traditional dietary recommendations for patients with chronic kidney disease (CKD) focus on the quantity of nutrients consumed. Without appropriate dietary counselling, these restrictions can result in a low intake of fruits and vegetables and a lack of diversity in the diet. Plant nutrients and plant-based diets could have beneficial effects in patients with CKD: increased fibre intake shifts the gut microbiota towards reduced production of uraemic toxins; plant fats, particularly olive oil, have anti-atherogenic effects; plant anions might mitigate metabolic acidosis and slow CKD progression; and as plant phosphorus has a lower bioavailability than animal phosphorus, plant-based diets might enable better control of hyperphosphataemia. Current evidence suggests that promoting the adoption of plant-based diets has few risks but potential benefits for the primary prevention of CKD, as well as for delaying progression in patients with CKD G3-5. These diets might also help to manage and prevent some of the symptoms and metabolic complications of CKD. We suggest that restriction of plant foods as a strategy to prevent hyperkalaemia or undernutrition should be individualized to avoid depriving patients with CKD of these potential beneficial effects of plant-based diets. However, research is needed to address knowledge gaps, particularly regarding the relevance and extent of diet-induced hyperkalaemia in patients undergoing dialysis.